The Movement of Female Journalists in News Coverage in Indonesia - Oktri Permata Lani; Novia Amirah Azmi (State Institute of Islamic Studies Batusangkar, 2023)
The world of media and the journalistic profession tend to be dominated by men, which can be called a macho atmosphere. The list of names of journalists known to the public are mostly filled by men. In contrast, for female workers, they are often placed in a more relaxed role as presenters in the studio or as editors who work behind the scenes. many places and opportunities, women often face injustice in society. The role of women is limited to sectors that are considered in accordance with their biological nature, belief system and certain culture, which causes gender inequality and injustice. This research method uses literature review and looks at existing cases and news.